Polygoni Multiflori Radix Praeparata Ethanol Extract Exerts a Protective Effect Against High-Fat Diet Induced Non-Alcoholic Fatty Liver Disease in Mice by Remodeling Intestinal Microbial Structure and Maintaining Metabolic Homeostasis of Bile Acids - Dai, Xuyang; He, Linfeng; Hu, Naihua; Guo, Chaocheng; Zhou, Mengting; Zhao, Xingtao; Wang, Cheng; Gong, Lihong; Ma, Cheng; Xue, Xinyan; Li, Yunxia (Frontiers in Pharmacology, 2021)
In the prescription of Traditional Chinese Medicine for lipid metabolism, Polygoni Multiflori Radix Preparata (ZhiHeShouWu, RPMP) was widely used. In recent years, RPMP ethanol extract has been reported for the treatment of non-alcoholic fatty liver disease (NAFLD). However, the role of RPMP ethanol extract in the treatment of NAFLD has not been fully elucidated. Therefore, we examined the optimal therapeutic dose of RPMP ethanol extracts. Afterward, a mouse model of non-alcoholic fatty liver induced by a high-fat diet (HFD) was treated with RPMP ethanol extract to further evaluate the mechanism of action of RPMP ethanol extract treatment. And the serum lipid metabolism indexes and liver function indexes showed that the RPMP ethanol extract in the 1.35 g/kg dose group exhibited better therapeutic effects than the 2.70 g/kg dose group. Meanwhile, RPMP ethanol extract can regulate the biochemical indicators of serum and liver to normal levels, and effectively reduce liver steatosis and lipid deposition. RPMP ethanol extract treatment restored HFD-induced disruption of the compositional structure of the intestinal microbial (IM) and bile acids (BAs) pools. And restore the reduced expression of intestinal barrier-related genes caused by HFD administration, which also effectively regulates the expression of genes related to the metabolism of BAs in mice. Thus, RPMP ethanol extract can effectively improve the abnormal lipid metabolism and hepatic lipid accumulation caused by HFD, which may be related to the regulation of IM composition, maintenance of intestinal barrier function, and normal cholesterol metabolism in the body.